Nadzom Sebagai Media Pendidikan dan Dakwah - Sukayat, Tata (IAIN Ponorogo, 2017)
Media is an objective tool that functions as a channel of communication which connects ideas with the audience. Nadzhom (Sundanese praises) is one of the media for connecting dawah messages with madu or lessons to learners. Generally, the values emerging from nadzoman cover aqidah education, worship, and morals. Nadzoman serve as effectiveness roles of dawah and Islamic education or Instructions. This research applied a library research as the design to analyze the literary materials in the form of nadzom related to its function as education media and dawah. The use of nadzoman could make the learners understand the material which were quite complicated, as they felt to be involved in learning while enjoying and singing the rhythm of beautiful nadzom verses. Nadzom has at least three functions, such as entertainment, education and dawah, and spiritual roles.Ø¥Ù Ø§ÙÙØ³ÙÙØ© â Ø£ÙÙØ§ ÙØ§ÙØª ÙØ¬ÙØ¯ÙØ§ â ÙÙ Ø¬ÙØ§Ø² ÙØ¥ÙØµØ§ÙÂ Ø§ÙØ¢Ø±Ø§Ø¡ Ø¥ÙÙ Ø§ÙØ¢Ø®Ø±ÙÙ. ÙÙØµÙØµ Ø§ÙÙØ¸Ù Ø¥ØØ¯Ù Ø§ÙÙØ³Ø§Ø¦Ù ÙØ¥ÙØµØ§Ù Ø±Ø³Ø§Ø¦Ù Ø§ÙØ¯Ø¹ÙØ© Ø¥ÙÙ Ø§ÙÙ Ø¯Ø¹ÙÙÙÙ Ø£Ù Ø¥ÙØµØ§Ù Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© Ø¥ÙÙ Ø§ÙØ·ÙØ§Ø¨. Ø£Ù Ø§ Ø§ÙÙÙÙ ÙÙ ÙØµÙØµ Ø§ÙÙØ¸Ù ÙØªØØªÙÙ Ø¹ÙÙ Ø§ÙÙÙÙ Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØ¹ÙØ¯ÙØ© ÙØ§ÙØ¹Ø¨Ø§Ø¯Ø© ÙØ§ÙØ£Ø®ÙØ§Ù. ÙÙØµÙØµ Ø§ÙÙØ¸Ù ØªØ¤Ø«ÙØ± ÙØ«ÙØ±Ø§ ÙÙ ÙØ¹ÙØ§ÙÙØ© Ø§ÙØ¯Ø¹ÙØ© ÙØ§ÙØªØ±Ø¨ÙØ© Ø£Ù ØªØ¹ÙÙÙ Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©. Ø§ØªÙØ¨Ø¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙ ÙØªØ¨ÙØ© ÙØ£Ø¬Ù ØªØÙÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø§ÙÙ ÙØªØ¨ÙØ© ÙÙÙ ÙÙ Ø´ÙÙ ÙØµÙØµ Ø§ÙÙØ¸Ù Ø¨Ø§ÙÙØºØ© Ø§ÙØ³ÙØ¯ÙÙØ© Ø§ÙÙ ØªØ¹ÙÙØ© Ø¨ÙØ¸ÙÙØªÙØ§ ÙØ£Ø¯Ø§Ø© ØªØ±Ø¨ÙÙØ© ÙØ¯Ø¹ÙÙØ©. ÙØ§Ø³ØªÙØ§Ø¯Ø© ÙØµÙØµ Ø§ÙÙØ¸Ù ØªØ¬Ø¹Ù Ø§ÙÙ ØªØ¹ÙÙÙ ÙÙ ÙÙ Ù Ø¬Ø§ÙØ³ Ø§ÙØªØ¹ÙÙÙ ÙØ§Ø¯Ø±ÙÙ Ø¹ÙÙ ÙÙÙ Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØµØ¹Ø¨Ø© ÙØ£ÙÙÙ ÙØ´Ø¹Ø±ÙÙ Ø¨Ø§ÙÙ Ø´Ø§Ø±ÙØ© ÙÙ Ø¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙÙ ÙØ¨Ø¬Ø§ÙØ¨ Ø°ÙÙ ÙÙ ÙØ³ØªÙ ØªØ¹ÙÙ ÙÙÙØ´Ø¯ÙÙ Ø£Ø¨ÙØ§Øª Ø§ÙÙØ¸Ù Ø§ÙØ´Ø§Ø¯Ø§ Ø¬Ù ÙÙØ§. ÙØ£Ø¨ÙØ§Øª Ø§ÙÙØ¸Ù ÙÙØ§ Ø«ÙØ§Ø« ÙØ¸Ø§Ø¦Ù : ÙØ¸ÙÙØ© Ø§ÙØªØ±ÙÙÙØ ÙÙØ¸ÙÙØ© Ø§ÙØªØ±Ø¨ÙØ©Ø ÙØ§ÙÙØ¸ÙÙØ© Ø§ÙØ±ÙØÙØ©.